Risk Factors for Hypertension in the Coastal Area of Konawe Regency: Hypertension - Nurul Aisyiah Rizal; Tasnim Tasnim; Erwin Azizi Jayadipraja (STIKes Mandala Waluya Kendari, 2023)
Background: Hypertension is a health problem in all parts of the world and is a major risk factor for cardiovascular disease. Konawe Regency is in second place after Muna as a district with the most hypertension sufferers in Southeast Sulawesi. The purpose of this study was to analyze the incidence of hypertension in the coastal area of Konawe Regency. Methods: This type of research uses quantitative methods with a case control study design. The population in this study amounted to 1,398 people, with a sample of 218 people. In this study, sampling was carried out by Cluster Sampling, with statistical tests using Odds Ratio. Results: The results of the OR 95% CI statistical test showed that there was a relationship between genetics (OR=3.204), salt consumption habits (OR=2.791), physical activity (OR=4.497), stress levels (OR=2.603), and smoking habits (OR=6.201) to the incidence of hypertension in the coastal area of Konawe Regency. Conclusion: It can be concluded that the risk factors for hypertension in the coastal area of Konawe Regency include genetics, salt consumption habits, physical activity, stress levels, and smoking habits. It is hoped that the health centre will collaborate with cross-sectors that are closest to the community such as health cadres and others, in efforts to detect here as well as counseling hypertension and certain other non-communicable diseases.